Hemoglobin phenotypes of children attending pediatric clinics in Lomé, Togo, 2022 - Yao Rodion Konu; Fiali Ayawa Lack; Oumarou I. Wone Adama; Harold Régis Kouanfack; Kokou Herbert Gounon; Kokou François Sogbo; Kodzovi Mawulé Corcellar Womey; Ounoo Elom Takassi; Maléwé Kolou; Didier Koumavi Ekouevi (BMC Research Notes)
Abstract Objective To provide an up-to-date data, we aim to estimate the frequency of sickle cell disease among children in the pediatric clinics of the Sylvanus Olympio University Hospital, Lome, Togo, in 2022. Results A total of 317 children with a median age of 8 years (Interquartile range: 4–12) were included. Both parents knew their Hb phenotype in 7.3% of cases. Nineteen children had sickle cell disease (6.0%) and about 15.6% of the children had sickle cell trait AS. This study found a high frequency of children with sickle cell disease seen in pediatric clinics. We therefore emphasize the need for continued education to improve knowledge of the hemoglobin phenotype at community level and the importance of premarital screening to reduce this burden in the country.